2019
DOI: 10.1002/cctc.201900953
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic H2 Evolution by the Co‐Mabiq Complex Requires Tempering of the Redox‐Active Ligand

Abstract: H2 is a promising fuel for sustainable energy conversion and storage. The development of effective earth abundant H2 evolution catalysts is integral to advancing hydrogen‐based technologies. H2 evolution by molecular complexes classically involves the formation of metal hydride intermediates. Recently, the use of redox‐active ligands has emerged as an alternate strategy for electron and proton storage. Herein, we examine the electrocatalytic behavior of [CoII(Mabiq)(THF)](PF6) (CoMbq), containing a redox‐activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…Hess and co-workers have reported a cobalt complex where three protons are required, with one of them acting as a pre-catalytic preparation of the complex. 25 This possibility could also take place in the kind of catalysts studied here. Table 2 shows that the p K a for a protonation of the second N d is favorable prior to a second reduction, regardless of the interactions with TFAH.…”
Section: Resultsmentioning
confidence: 82%
“…Hess and co-workers have reported a cobalt complex where three protons are required, with one of them acting as a pre-catalytic preparation of the complex. 25 This possibility could also take place in the kind of catalysts studied here. Table 2 shows that the p K a for a protonation of the second N d is favorable prior to a second reduction, regardless of the interactions with TFAH.…”
Section: Resultsmentioning
confidence: 82%
“…Current challenges include the design of new catalytic platforms featuring higher activity together with increased stability. Introduction of proton relays in the second coordination sphere of the metal center or redox-active ligands have been proved essential to promote, tune, or enhance catalytic activity. Notable examples involve the control of the formation of cobalt-hydride derivatives as the key active species in catalysis. Recently, cobalt­(II) polypyridyl complexes have emerged as promising catalysts for hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…One of us has previously developed the solution chemistry of a series of mono- and bimetallic Mabiq complexes. Monometallic M-Mabiq complexes (e.g., M = Fe, Co, Ni, Cu, and Zn) with formal oxidation states ranging from 0 to III were isolated. Our studies demonstrated that both the mono- and bimetallic compounds are photoactive. , Notably, the Co-Mabiq complex acts as an electrocatalyst for H 2 evolution, while Ni-Mabiq enables photocatalytic C–C bond formation. , …”
Section: Introductionmentioning
confidence: 78%